Colombia : Financial Sector Assessment Program-Technical Note on Risk Analysis. (IMF Staff Country Reports; Country Report ;, 2022)
The Financial Sector Assessment Program (FSAP) risk analysis work was conducted in the aftermath of the initial COVID shock and subsequent lockdowns, and while a strong economic recovery was underway in Colombia during 2021. Given the persistent uncertainty around the evolution of the COVID-19 virus, and for the trajectory of the economic recovery, the outlook remained subject to significant revisions throughout the year. While the workstreams took the latest macroeconomic and supervisory data updates into account as much as possible for the various analyses, the test results and their implications should be interpreted with caution due to high uncertainty around the central projections and downside risks.